2015
DOI: 10.1002/aenm.201500646
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Manganese Dissolution from Lithium Manganese Oxide Spinel Cathodes with Single‐Layer Graphene

Abstract: Spinel-structured LiMn 2 O 4 (LMO) is a desirable cathode material for Li-ion batteries due to its low cost, abundance, and high power capability. However, LMO suffers from limited cycle life that is triggered by manganese dissolution into the electrolyte during electrochemical cycling. Here, it is shown that single-layer graphene coatings suppress manganese dissolution, thus enhancing the performance and lifetime of LMO cathodes. Relative to lithium cells with uncoated LMO cathodes, cells with graphene-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 61 publications
2
75
0
1
Order By: Relevance
“…Among the coatings that have been widely tested experimentally, and often found to yield sufficient protection122225262728293031323337, MgO, ZrO 2 , and Ta 2 O 5 are in the top 30 HF-scavenger lists in Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the coatings that have been widely tested experimentally, and often found to yield sufficient protection122225262728293031323337, MgO, ZrO 2 , and Ta 2 O 5 are in the top 30 HF-scavenger lists in Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…While alternative strategies such as doping171819, tailoring the particle morphology2021 or core–shell structures222324 have been suggested, a common approach to suppressing cathode degradation has been applying protective coatings on cathode particles1222252627282930313233. Stable binary oxides, such as Al 2 O 3 , MgO, ZnO, ZrO 2 , SiO 2 and TiO 2 may reduce the HF-content in the electrolyte123435, but their performance in suppressing the transition metal-loss from the cathode or the capacity fade can vary significantly2736.…”
mentioning
confidence: 99%
“…To stabilize the cathode–electrolyte interface, surface coating of cathode materials by using electrochemically inert species has been widely practiced . Metal oxides and metal phosphates have been tested thoroughly as coating species in light of their extraordinary stability at high voltage as far as both their chemical and electrochemical stability are concerned.…”
Section: Precise Surface Control Of Cathode Materialsmentioning
confidence: 99%
“…In order to solve this problem, surface modification of the cathode electrode is an effective way to reduce the side reactions. It was reported that the single-layer graphene can suppress Mn dissolutions of LMO cathode [53] by blocking Mn diffusion and the oxidation state of surface Mn. Mn dissolution is a possible problem for the usage of MMO and MNMO as cathode for MIBs.…”
Section: (B)mentioning
confidence: 99%